Improvement of channel property of GaN vertical trench MOSFET by compensating nitrogen vacancies with nitrogen plasma treatment. (4th December 2020) - Ishida, Takashi; Pil Nam, Kyung; Matys, Maciej; Uesugi, Tsutomu; Suda, Jun; Kachi, Tetsu
Abstract: The electrical properties of vertical GaN trench MOSFETs without drift layers were evaluated to investigate the effect of nitrogen plasma treatment on the trench sidewalls. It is demonstrated that nitrogen plasma treatment improves the channel property of the vertical GaN trench MOSFET. The possible mechanism of this improvement is the supply of nitrogen atoms from nitrogen plasma treatment to the trench surfaces, and the compensation of the nitrogen vacancies near the trench surfaces by the nitrogen atoms during gate oxide annealing. The temperature dependence and the limiting factors of the channel property are also discussed.